Penerapan strategi directed listening thinking activity (DLTA) untuk meningkatkan keterampilan menyimak teks deskripsi kelas II sekolah dasar - Ayuning Tias Lila; Rukayah Rukayah; Tri Budiharto (Universitas Sebelas Maret, 2023)
The purpose of this research are: 1) to improve listening skill through the application of Directed Listening Thinking Activity strategy, and 2) to describe the result of application Directed Listening Thinking Activity strategy. This research is classroom action research with two cycles. The subject of this reseach were student of the 2nd student at State Primary School Pajang 2 no. 171 Surakarta in the 2019/2020 academic year, totalling 26 student. The research uses data collect technique in the form of interview, observation, analysis of documentation and test with data analysisof content validity, technical triangulation and source triangulation. The analysis of the data used is describe comparative analysis and the interactive analysis model of Miles-Huberman. The first cycle resulting in a percentage of 53,84% in classical, and the study continued with the second cycle with the percentage of 84,61% in classical terms. The conclude is the ability to solve skill listening on 2nd student at Primary School 2 Pajang 2 no. 171 Surakarta in the 2019/2020 academic year can be improved throught the Directed Listening Thinking Activity Strategy.